Plasma ceramide, a real-time predictive marker of pulmonary and hepatic metastases response to stereotactic body radiation therapy combined with irinotecan - Dubois, Nolwenn; Rio, Emmanuel; Ripoche, Natacha; Ferchaud-Roucher, Véronique; Gaugler, Marie-Hélène; Campion, Loic; Krempf, Michel; Carrie, Christian; Mahé, Marc; Mirabel, Xavier; Paris, François (Radiotherapy and oncology, 2016)
Early biomarkers of tumour response are needed to discriminate between responders and non-responders to radiotherapy. We evaluated the ability of ceramide, a bioactive sphingolipid, to predict tumour sensitivity in patients treated by hypofractionated stereotactic body radiation therapy (SBRT) combined with irinotecan chemotherapy. Plasma levels of total ceramide and of its subspecies were measured before and during treatment in 35 patients with liver and lung oligometastases of colorectal cancer included in a phase II trial. Cer levels were quantified by LC–ESI-MS/MS and compared to tumour volume response evaluated one year later by CT-scan. Pretreatment plasma ceramide levels were not indicative of tumour response. Nevertheless, the levels of total ceramide and of its 4 main subspecies were significantly higher at days 3 and 10 of treatment in objective responders than in non-responders. According to Kaplan–Meier curves, almost complete tumour control was achieved at 1year in patients with increased total ceramide levels whereas 50% of patients with decreased levels experienced an increase in tumour volume. Total plasma ceramide is a promising biomarker of tumour response to SBRT combined with irinotecan that should enable to segregate patients with high risk of tumour escape.